2021
DOI: 10.2147/opth.s298209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laterality on Cumulative Survival in Patients Diagnosed with Retinoblastoma: A Retrospective Cohort Analysis of 1925 Cases in the Surveillance, Epidemiology, and End Results (SEER) Program

Abstract: Background Retinoblastoma is an intraocular cancer with potentially severe clinical consequences if left untreated. Diagnostic and clinical management guidelines are strictly dependent on nature of laterality. This analysis aims to characterize the influence of laterality on survival in patients diagnosed with retinoblastoma. Methods This retrospective cohort analysis utilized the Surveillance, Epidemiology, and End Results (SEER) program for population-based clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Differences in L/R bilateral tumors have been reported for several cancer types, like breast (Kenney et al 2004 ; Garfinkel et al 1959 ), colon (Yang et al 2018 ; Baran et al 2018 ; Sponholz et al 2021 ), kidney (Ni et al 2021 ; Guo et al 2019 ), brain (Połczyńska et al 2021 ), ovary (He et al 2021 ), and eye (Hussain 2021 ). Particularly in breast tumors, in addition to the largely known increased L-side incidence (Busk and Clemmensen 1947 ; Roychoudhuri et al 2006 ), interesting differences in gene expression (Robichaux et al 2014 ; Mittwoch 2008 ), gland microbiota (Klann et al 2020 ), mitochondria distribution (Mishra and Chan 2014 ) and methylation profiles (Campoy et al 2016 ) have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Differences in L/R bilateral tumors have been reported for several cancer types, like breast (Kenney et al 2004 ; Garfinkel et al 1959 ), colon (Yang et al 2018 ; Baran et al 2018 ; Sponholz et al 2021 ), kidney (Ni et al 2021 ; Guo et al 2019 ), brain (Połczyńska et al 2021 ), ovary (He et al 2021 ), and eye (Hussain 2021 ). Particularly in breast tumors, in addition to the largely known increased L-side incidence (Busk and Clemmensen 1947 ; Roychoudhuri et al 2006 ), interesting differences in gene expression (Robichaux et al 2014 ; Mittwoch 2008 ), gland microbiota (Klann et al 2020 ), mitochondria distribution (Mishra and Chan 2014 ) and methylation profiles (Campoy et al 2016 ) have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…This can be from factors cited earlier on the similarity of International Retinoblastoma Staging System stages between patients with unilateral and bilateral disease. Generally, patients with unilateral disease were found to have higher survival rates compared to those with bilateral disease, with the latter having a 1900% increased hazard risk [39][40] . Another series attributed this to higher proportion of extraocular disease and increased incidence of secondary neoplasms among those with bilateral disease [41] .…”
Section: Discussionmentioning
confidence: 97%
“…Differences in L/R bilateral tumors have been reported for several cancer types, like breast [36], [37], colon [9], [38], [39], kidney [40], [41], brain [42], ovary [43], and eye [44]. Particularly in breast tumors, in addition to the largely known increased L-side incidence [45] [46], interesting differences in gene expression [8] [33], gland microbiota [47], mitochondria distribution [48] and methylation profiles [10] have been reported.…”
mentioning
confidence: 99%